2008
DOI: 10.1021/jf802279h
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Behavioral Effects of Stilbene Resveratrol Analogues: Implications for Reducing the Deleterious Effects of Aging

Abstract: Research suggests that polyphenolic compounds contained in fruits and vegetables that are rich in color may have potent antioxidant and anti-inflammatory activities. The present studies determined if stilbene (e.g., resveratrol) compounds would be efficacious in reversing the deleterious effects of aging in 19 month old Fischer 344 rats. Experiment I utilized resveratrol and six resveratrol analogues and examined their efficacies in preventing dopamine-induced decrements in calcium clearance following oxotremo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 40 publications
1
112
0
2
Order By: Relevance
“…The structure of the product 5 was identified by direct comparison of its NMR spectra with the reported data. 28) Thus, compound 5 was determined to be pterostilbene 4′-β-glucopyranoside (glucoside).…”
Section: Resultsmentioning
confidence: 99%
“…The structure of the product 5 was identified by direct comparison of its NMR spectra with the reported data. 28) Thus, compound 5 was determined to be pterostilbene 4′-β-glucopyranoside (glucoside).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, there are no reported estimates regarding pterostilbene intake in humans. Joseph et al [179] have reported that dietary pterostilbene is effective in reversing cognitive deficits in aged rats with a correlation with hippocampal pterostilbene levels. Quite recently, it has been shown that, at equivalent and diet-achievable doses, pterostilbene is a more potent modulator of cognition and cellular stress than resveratrol, likely driven by increased peroxisome proliferator-activated receptor alpha (PPAR-␣) expression and the aforementioned methoxy moiety [180].…”
Section: Effects On Age-related Cognitive Declinementioning
confidence: 99%
“…Furthermore, its anti-metastatic efficacy was demonstrated in a mouse model with highly malignant B16 F10 melanoma cells (Ferrer et al, 2005). Besides anti-cancer effects, other resveratrol-like activities, including analgesia (Remsberg et al, 2008), anti-ageing (Joseph et al, 2008), anti-diabetic (Amarnath Manickam et al, 1997;Pari and Satheesh, 2006), anti-inflammation (Hougee et al, 2005;Pan et al, 2008a) (Remsberg et al, 2008), anti-obesity (Rimando et al, 2005), anti-oxidation (Amarnath Kim et al, 2009;Perecko et al, 2008;Remsberg et al, 2008;Rimando et al, 2002) and neuro-protection (Joseph et al, 2008;Meng et al, 2008;Pan et al, 2008a), have also been reported.…”
Section: Introductionmentioning
confidence: 98%